Case report: Rapid clinical improvement of anti-HMGCR immune-mediated necrotizing myopathy treated with efgartigimod - Zeng, Quantao; Chen, Kai; Zeng, Li; Xu, Lixia; Tan, Song (Frontiers in Immunology, 2024)
Immune-mediated necrotizing myopathy (IMNM) with anti-HMGCR antibody positivity is characterized by proximal extremity weakness, increased creatine kinase, and extensive muscle edema. There is an urgent need to find more appropriate treatment options for anti-HMGCR IMNM patients who do not respond well to conventional therapy in the acute phase. With the advent of targeted biologics, new treatment options are available. We report on a 66-year-old anti-HMGCR IMNM patient who initially presented with a 1-month history of progressive proximal extremity weakness and dysphagia with markedly elevated creatine kinase. The patient did not respond to conventional high-dose glucocorticoid and intravenous immunoglobulin therapy, and his symptoms rapidly deteriorated over the 2 weeks after this treatment, with worsening limb weakness that prevented walking, marked proximal muscle atrophy, and weight loss. After one cycle (four infusions) of efgartigimod, the patient’s symptoms improved markedly and he has since (for several months) remained in a good clinical state.